Peningkatan Keaktifan Siswa Kelas 2C di MI Nurussalam pada Materi Akidah Akhlak Melalui Pendekatan Auditori-Somatis-Visual-Intelektual (ASVI) - Alinda Zakiyatul Fakhiroh; Lutfia Zaina (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2021)
Abstract: This study aims to improve student learning activeness by applying the Auditory-Somatic-Visual-Intellectual (ASVI) approach. This research is a Class Action Research conducted in two cycles. Where each cycle consists of planning, implementation, observation, and reflection. Data collection techniques carried out are with and non tests (observation, interviews, and questionnaires). Data analysis used qualitative descriptive analysis techniques. The results of class action research with the application of the ASVI approach show that: the completeness of student activity in the first cycle was 66.2% and experienced an increase in the second cycle of 78.2%. Thus, the activeness of the 2C class students in akidah akhlak lesson after the implementation of the Auditory-Somatic-Visual-Intellectual (ASVI) approach was applied has increased from each cycle of 12%.